I’RĀB AL-QUR’AN DAN URGENSINYA TERHADAP PENENTUAN HUKUM FIQH - Maulana, Ihsan (Al-Fath, 2022)
The Qur'an was revealed in Arabic. It is undeniable that Arabic has a function to clarify a meaning. While the way to get it is by using i'rab. Therefore, i'rāb has a relationship with Islamic sciences such as Tafsir, Qira'at, and Fiqh. In fiqh, there are many laws that are still being debated by 'Ulama because of differences in i'rab. This study examines the effect of differences in i'rāb on istinbath (excavation) of fiqh laws from verses of the Qur'an. The certainty that the difference in i'rāb is based on the meaning contained in the science of Nahwu. If they have different opinions in determining the topic of sentences contained in the verses of the Qur'an, absolutely these differences can affect our understanding and we can be sure that the meaning resulting from each opinion will be different from the others. In this case, the researcher discusses the differences in legal verses that sometimes affect fiqh laws determined by experts, as well as some of the factors behind differences in determining fiqh laws which are also related to differences in i'rāb itself.